Epidemiological study of Cryptosporidiosis in (Anser anser domestics geese) in Nineveh Governorate - غانم رواء (University of Thi-Qar Journal of Science, 2010)
The results of this study reveal that the total percentage of infection with Cryptosporidium spp. in geese in Nineveh governorate was 46.67% the infection was highest during spring %68 and lowest during summer 20% . No significant differences recorded between females and males since the rates of infection were 47.76% and 43.47% respectively .The higher percentages of infection was in Tobzawa village while the lowest was in Mosulcity. The current study showed that the sensitivity of modified acid fast stain (hot stain) was very high % 100 while the percentage with sheather’s sugar solution and iodine Methods were %69 .0 4 and% 88. 09 respectively .